Analisis Faktor-Faktor yang Mempengaruhi Adiksi Pada MMORPG (Studi Kasus: Final Fantasy XIV) - Reihan Putra; Betty Purwandari; Riri Satria (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
The number of video game players worldwide escalates yearly. The easy access to games has undeniably led many individuals to experience addiction. In 2019, the World Health Organization (WHO) officially classified game addiction as a disease. Among the various genres, the Massive Multiplayer Online Role-Playing Game (MMORPG) genre stands out as one of the most addictive. The MMORPG game dominating the market is Final Fantasy XIV, boasting an impressive player base of 27 million. This study aims to identify factors driving addiction to Final Fantasy XIV. The research adopts the MMORPG Affordance theory and Motivation Factors as the underlying research model. Out of 132 valid questionnaire responses, three hypotheses emerge as statistically significant in influencing addiction. The findings of this study offer valuable insights for policymakers and decision-makers, enabling them to devise strategies to prevent MMORPG addiction and foster a healthy virtual environment conducive to productivity